Cellulose degradation products and high ionic strength enhance the retardation of strontium in hydrated cement paste - Hinchliff, J.; Felipe-Sotelo, M.; Drury, D.; Evans, N.D.M.; Read, D. (Frontiers in Nuclear Engineering, 2022)
The present concept for the disposal of some low- and all intermediate-level radioactive waste in the UK involves grouting with cement in steel drums and placement in a geological facility. The vaults would then be backfilled with a low strength, high porosity cement designed to promote a pervasive, alkaline environment in which many of the radioactive species present are sparingly soluble. This work investigates the interaction of strontium with such a backfill under both diffusive and advective conditions given the potential significance of the fission product 90Sr. An important characteristic of the UK waste inventory is the abundance of organic compounds, including cellulosic materials; consequently, the experiments were repeated with products of alkaline cellulose degradation. Additional experiments were performed at high ionic strength simulating anticipated changes in the salinity of the groundwater. The diffusivity of strontium in the absence of the organic compounds ranged between 5.5 × 10-11 and 8.5 × 10-11 m2 s-1, with a partition coefficient of between 2.8 × 10-3 and 3.1 × 10-3 m3 kg-1. The presence of organic compounds and/or an increase of ionic strength enhanced the retardation of strontium. The results indicate that the retention of strontium by cement occurs via a reversible ion exchange mechanism rather than mineralisation and is promoted by decalcification of the calcium silicate hydrate phases in the cement.